Thermoeconomic analysis of a solar driven heat engine - Sahin, B; Ust, Y; Yilmaz, T; Akcay, IH (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
Thermoeconornic optimization has been carried out for an endoreversible solar driven heat engine using finite-time/finite-size thermodynamic theory. In the considered heat engine model, heat transfer from the hot reservoir is assumed to be radiation mode and the heat transfer to the cold reservoir is assumed to be convection mode. The power output per unit total cost is taken as objective function and the optimum performance and design parameters have been investigated. The effects of the technical and economical parameters on the thermoeconomic performances have been also discussed. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: endoreversible; thermoeconomic performance; optimization; solar-driven heat engine; PERFORMANCE ANALYSIS; MAXIMUM POWER; EFFICIENCY; OPERATION; DESIGN; Science & Technology - Other Topics; Energy & Fuels